Winter cancellations of elective surgical procedures in the UK: a questionnaire survey of patients on the economic and psychological impact. Issue 9 (13th September 2019) - Herrod, Philip J J; Adiamah, Alfred; Boyd-Carson, Hannah; Daliya, Prita; El-Sharkawy, Ahmed M; Sarmah, Panchali B; Hossain, Tanvir; Couch, Jennifer; Sian, Tanvir S; Wragg, Andrew; Andrew, David R; Parsons, Simon L; et al.
Abstract : Objectives: To quantify the economic and psychological impact of the cancellation of operations due to winter pressures on patients, their families and the economy. Design: This questionnaire study was designed with the help of patient groups. Data were collected on the economic and financial burden of cancellations. Emotions were also quantified on a 5-point Likert scale. Setting: Five NHS Hospital Trusts in the East Midlands region of England. Participants: We identified 796 participants who had their elective operations cancelled between 1 November 2017 and 31 March 2018 and received responses from 339 (43%) participants. Interventions: Participants were posted a modified version of a validated quality of life questionnaire with a prepaid return envelope. Main outcome measures: The primary outcome measures were the financial and psychological impact of the cancellation of elective surgery on patients and their families. Results: Of the 339 respondents, 163 (48%) were aged <65 years, with 111 (68%) being in employment. Sixty-six (19%) participants had their operations cancelled on the day. Only 69 (62%) of working adults were able to return to work during the time scheduled for their operation, with a mean loss of 5 working days (SD 10). Additional working days were lost subsequently by 60 (54%) participants (mean 7 days (SD 10)). Family members of 111 (33%) participants required additional time off work (mean 5 days (SD 7)). Over 30% of participants reported extreme levels of sadness, disappointment, anger, frustration and stress. At least moderate concern about continued symptoms was reported by 234 (70%) participants, and 193 (59%) participants reported at least moderate concern about their deteriorating condition. Conclusions: The cancellation of elective surgery during the winter had an adverse impact on patients and the economy, including days of work lost and health-related anxiety. We recommend better planning, and provision of more notice and better support to patients.